Quercetin inhibition of myocardial fibrosis through regulating MAPK signaling pathway via ROS - Min, Zhang; Yangchun, Li; Yuquan, Wang; Changying, Zhang (Pakistan journal of pharmaceutical sciences, 2019)
Mitogen-activated protein kinase (MAPK) cascades are important players in the cellular signal pathways, and the deregulation of MAPKs is involved in a variety of diseases, especially cardiovascular disorders. This study was designed to investigate the effects of quercetin on proliferation of cardiac fibroblasts, measured the secretion of Col I & Col III by ELISA and the expression of extra cellular-signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK) p38 by eastern blotting in cardiac fibroblasts challenged with angiotensin (Ang-II). Results showed that Ang-II significantly increased the DNA synthesis and collagen secretion. In contrast, quercetin reversed such effects and inhibited cardiac fibroblasts proliferation. Furthermore, reactive oxygen species (ROS) stimulated the phosphorylation of ERK, p38 and JNK, while pre-administration of quercetin significantly (P<0.05) reduced the phosphorylation. All these evidences revealed that quercetin inhibited the MAPK pathway activation via ROS.